Quantum Dynamics Simulations on the Adsorption Mechanism of Reducing and Oxidizing Gases on the CH3NH3PbI3 Surface. Issue 5 (29th March 2020) - Tong, Lei; Zhang, Bing; Wang, Xiaogang G.; Liao, Yinjie J.; Yang, Jieqin Q.
Abstract: Existing experiments have revealed that methylammonium lead iodide (MAPbI3 or CH3 NH3 PbI3 ) materials show favorable gas‐sensing properties to reducing gas NH3 and oxidizing gases O2 and O3 . The first step to effective gas‐sensing by using semiconductor materials for gas‐sensing applications is to recognize a target gas through gas–solid interaction. To explore the sensing mechanisms of perovskite materials to different oxidizing and reducing gases, the changes of skeleton structures of MAPbI3 in reducing gas NH3 and oxidizing gases O2 and O3, adsorption energy, and charge transfer between gases and semiconductors are investigated through large‐scale quantum dynamics simulations. By using three adsorption models, the differences and similarities of adsorption mechanisms of MAPbI3 for gases NH3, O2, and O3 are illustrated. These adsorption mechanisms are expected to provide new ideas for developing innovative sensing elements made of perovskite materials with stronger stability, high sensitivity, and high selectivity. Abstract : The different adsorption processes of CH3 NH3 PbI3 for the reducing gas NH3 and the oxidizing gases O2 and O3 are simulated by employing ab initio molecular dynamics in the current work. The adsorption characteristics are described via the changes of structures of perovskite materials, adsorption energy, and charge transfer between semiconductors and gas molecules along the dynamics process.